Here Today, Outsourced Tomorrow:Knowledge Workers in the Global Economy - Mosco, Vincent (Javnost-The Public, 2005)
Outsourcing of jobs, particularly the growing practice of sending the jobs of U.S. knowledge and communication sector workers to other countries, has become a significant issue in academic, policy and media circles. The paper begins by defining knowledge workers and summarising debates about their significance dating from the 1950s. Next it considers prevailing views about the problem which centre on the fear of massive job loss to low-wage nations like India and China and prevailing solutions offered by labour- stop outsourcing wherever possible, and by business outsourcing can only be curtailed when business and labour grow smarter. Each of these views conveys an essential truth but each deals only with symptoms of a significant transformation in the international division of labour. Understanding this transformation, and the role of information and communication technologies, leads us to consider key dimensions in the complexity of outsourcing: developed nations like Canada and Ireland have benefited as recipients of outsourced jobs; less developed nations like India are not just recipients of outsourced jobs, they are beginning to lead the process; in spite of ‘end of geography’ promises, place matters and culture counts; and, finally, resistance takes a multiplicity of forms.